Winter activity of boreal bats - Blomberg Anna S.; Vasko Ville; Meierhofer Melissa B.; Johnson Joseph S.; Eeva Tapio; Lilley Thomas M. (SPRINGER HEIDELBERG, 2022)
Natural hibernation sites used by bats in areas that lack cave features have long remained unresolved. To investigate hibernation site selection and winter activity of boreal bats, we recorded bat calls using passive acoustic monitoring at 16 sites in South-Western Finland. These sites included four rock outcrops with crevices and cave features, three glacial erratics or boulder fields, three ancient shores, three root cellars and three control sites where we did not expect bats to be overwintering. Our results revealed echolocation calls of Eptesicus nilssonii, Plecotus auritus and Myotis sp. We recorded significantly more activity near rock outcrops compared to other habitats, excluding root cellars. We also found that ambient temperature had a positive effect on bat activity and found evidence that P. auritus may be using low barometric pressure as a proxy for suitable foraging conditions during the winter. Our results suggest that rock outcrops may be more important to bats than previously acknowledged, highlighting the need to take these sites in account in planning of conservation measures. Furthermore, our findings underline the suitability of using acoustic monitoring in homing on hibernation sites that are not otherwise accessible.